CURRICULUM MANAGEMENT AS CUSTOMER TRUST IN THE QUALITY OF MEMORIZATION OF QUR'AN STUDENT - Basid, Abd.; Kusumawati, Ida (Managere: Indonesian Journal of Educational Management, 2022)
This study aims to determine the improvement of the quality of memorization of the Qur'an where the number of students who memorize the Qur'an is not following the rules of tajweed and less than optimal quantity and quality of memorization is the focus of this study. This research method aims to determine the effectiveness and quality of memorization of the Qur'an students to find out changes before using the curriculum and after using the curriculum. This study used a qualitative approach and data collection techniques in this study using observation and interviews. Data analysis used is data display, data reduction, and decisions taken. From the results of the study, it can be concluded that the overall curriculum process applied in the Tahfidz Program runs well and can increase the quantity and quality of memorization of the Qur'an students. Although there are some technical obstacles, the existence of a curriculum can help in improving the quality of memorization of the Qur'an students and increasing customer trust in the surrounding environment and community.